2009
DOI: 10.1007/s00467-009-1264-0
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine and steroid therapy in children with steroid-resistant nephrotic syndrome

Abstract: We conducted a prospective, multicenter trial to evaluate the efficacy and safety of a 12-month course of cyclosporine in children with steroid-resistant nephrotic syndrome (SRNS). Thirty-five patients were enrolled, of whom 28 had minimal change or diffuse mesangial proliferation (MC/DMP), and seven had focal segmental glomerulosclerosis (FSGS). All patients received cyclosporine and prednisolone; patients with FSGS additionally received methylprednisolone pulse therapy (MPT). The dose of cyclosporine was adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
3
4

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 31 publications
4
53
3
4
Order By: Relevance
“…MMF is a promising therapeutic alternative without nephrotoxicity [20]. But there is no single consensus regarding the indications of renal biopsy and treatment protocols in children with SRNS [13,14,15,16]. Optimal combinations of these agents with the least toxicity remain to be determined [12].…”
Section: Discussionmentioning
confidence: 99%
“…MMF is a promising therapeutic alternative without nephrotoxicity [20]. But there is no single consensus regarding the indications of renal biopsy and treatment protocols in children with SRNS [13,14,15,16]. Optimal combinations of these agents with the least toxicity remain to be determined [12].…”
Section: Discussionmentioning
confidence: 99%
“…Also, in Saudi Arabia and Tunisie (countries comparable to Egypt), the incidence of FSGS is more important than MCD in steroid-resistant cases. 23,24 However, two studies from Japan and France reported a significantly higher incidence of MCD compared to FSGS in steroid-resistant NS. 11,24 The reasons for disparities in the frequency of MCD and FSGS are not entirely clear.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 However, two studies from Japan and France reported a significantly higher incidence of MCD compared to FSGS in steroid-resistant NS. 11,24 The reasons for disparities in the frequency of MCD and FSGS are not entirely clear. They are probably explained by racial, genetic and environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…Estos cambios van desde la toxicidad aguda y la vacuolización isomérica de las células epiteliales tubulares hasta la fibrosis intersticial renal en un 80% de ellos cuando el tratamiento se prolonga por 4 años. [42][43][44][45][46] Los últimos resultados publicados aportan una remisión de la proteinuria en un 80% en pacientes corticorresistentes con esclerosis focal. [46][47][48] Otras recomendaciones para el tratamiento de pacientes que no responden a la ciclofosfamida son ácido micofenólico, tacrolimos y rituximab.…”
Section: Ciclofosfamida Sensibleunclassified